Examination of self-efficacy levels of tourist guides - Arpacı, Suat (Nevsehir Haci Bektas Veli University, 2022)
The aim of this study is to determine the self-efficacy levels of tourist guides according to demographic variables. A self-efficacy scale consisting of 10 unidimensional expressions was used to measure the self-efficacy levels of tourist guides. Convenience sampling method was used as the sampling method. In this context, a questionnaire was applied to active tourist guides affiliated to Aydın Guides Chamber. Of the 315 returned questionnaires, 300 questionnaires were considered suitable for data analysis. In the analysis of the data, independent groups t-test, one-way analysis of variance (anova) and were used. When the answers given by the guides regarding the self-efficacy variable are examined, it can be said that the self-efficacy perceptions of professional tourist guides are high. As a result of the analysis, it was determined that the self-efficacy levels of the tourist guides differed significantly according to the type of work card, education level and professional experience.

Bu çalışmanın amacı, turist rehberlerinin öz yeterlilik düzeylerinin demografik değişkenlere göre belirlenmesidir. Turist rehberlerinin öz yeterlilik düzeylerini ölçmek için daha önce geliştirilen tek boyutlu 10 ifadeden oluşan öz yeterlilik ölçeği kullanılmıştır. Örneklem yöntemi olarak kolayda örneklem yöntemi kullanılmıştır. Bu bağlamda, Aydın Rehberler Odasına bağlı eylemli turist rehberlerine anket uygulanmıştır. Geri dönüşümü gerçekleşen 315 anketten 300 anket verilerin analizi için uygun olarak değerlendirilmiştir. Verilerin analizinde, bağımsız gruplar t testi, tek yönlü varyans analizi (anova) ve kullanılmıştır. Öz yeterlilik değişkenine ilişkin, rehberlerin vermiş olduğu cevaplar incelendiğinde profesyonel turist rehberlerinin öz yeterlilik algılarının yüksek olduğu söylenebilir. Yapılan analizler sonucunda turist rehberlerinin öz yeterlilik düzeylerinin çalışma kartı türü, eğitim durumu ve mesleki deneyime göre anlamlı farklılık gösterdiği tespit edilmiştir.
Turist rehberlerinin öz yeterlilik düzeylerinin incelenmesi
Keywords: Tourism (Other); Turizm (Diğer)